Preservation of Oil Palm Fruits: Nonoxidative Effects of Ionizing Radiation on Palm Olein and Crude Palm Oil - Endinkeau, Kuang; Woodward, T. W. (1989)
The effect of gamma-irradiation on palm oil has been investigated. Irradiation doses (0.1 to 1 MGj') caused severe destruction of unsaturated but had little effect on saturated fatty acids. Similar effects were obsemed in irradiated samples stored for 1 and 2 months at room temperature. Radiation (uP to 30 kGy) also caused severe destruction of carotenes in crude palm oil, but had no significant effect on the free fatty acid content. These findings indicate that gamma-radiation may be used for preservation but not for sterilization of palm fruits.